2016
DOI: 10.3389/fcell.2016.00027
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Hypoxia-Mediated Tumor Progression: Combinatorial Approaches Targeting pH Regulation, Angiogenesis and Immune Dysfunction

Abstract: Hypoxia is an important contributor to the heterogeneity of the microenvironment of solid tumors and is a significant environmental stressor that drives adaptations which are essential for the survival and metastatic capabilities of tumor cells. Critical adaptive mechanisms include altered metabolism, pH regulation, epithelial-mesenchymal transition, angiogenesis, migration/invasion, diminished response to immune cells and resistance to chemotherapy and radiation therapy. In particular, pH regulation by hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 166 publications
0
97
0
Order By: Relevance
“…For example, carbonic anhydrase IX (CA‐IX) controls intracellular and extracellular acid–base balance to maintain survival and is a key regulator of extracellular acidity. As a catalyser of reversible hydration of CO 2 to bicarbonate and protons at the extracellular surface, inhibition of the catalytic activity of CA‐IX can manipulate its role in pH regulation . Lactate overproduction is another hallmark of cancer that is associated with acidity and can impact a cell's ability to regulate its pH in the face of acidity .…”
Section: Targeting Hypoxia and Acidosis To Improve Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, carbonic anhydrase IX (CA‐IX) controls intracellular and extracellular acid–base balance to maintain survival and is a key regulator of extracellular acidity. As a catalyser of reversible hydration of CO 2 to bicarbonate and protons at the extracellular surface, inhibition of the catalytic activity of CA‐IX can manipulate its role in pH regulation . Lactate overproduction is another hallmark of cancer that is associated with acidity and can impact a cell's ability to regulate its pH in the face of acidity .…”
Section: Targeting Hypoxia and Acidosis To Improve Immunotherapymentioning
confidence: 99%
“…In contrast to the belief that stromal cells use only glucose as an energy source, it was demonstrated that they also can use cancer‐cell‐derived lactate, which is transported into cells primarily with MCT‐1 . There is a strong effort to target MCTs, and these approaches may be combined with immune therapies by virtue of their effects on pH regulation . Targeting lactate metabolism is another promising approach for the modulation of tumour pH.…”
Section: Targeting Hypoxia and Acidosis To Improve Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these proteins may also act as signaling molecules to modulate the local microenvironment, creating a pro-metastatic environment, and trigger an angiogenic and desmoplastic response via a complex reciprocal dialogue between the tumor cells and the cells of the colonized organ (15,16). In addition to the tissue cells, immune populations recruited from the circulation during metastasis formation are also involved in generating a favorable environment for metastatic growth (17,18). Therefore, determining the role of adhesion molecules during the different stages of this process remains a major goal for our understanding of the metastatic cascade.…”
Section: Introductionmentioning
confidence: 99%
“…This is made possible by a cellular HIF system. Cellular hypoxia, or a lower than "normal" concentration of O 2 in cells, occurs commonly and could induce signiicant changes, immediate or delayed, on cellular processes, including cell growth and apoptosis, cell proliferation and survival, pH regulation and energy metabolism, cell migration, matrix and barrier function, angiogenesis, and vasomotor regulation [8][9][10][11][12][13]. These biological processes involve active responses by the body to secure an additional oxygen supply via circulation.…”
Section: Hypoxia In the Oral/periodontal Environmentmentioning
confidence: 99%